Peran Hukum dalam Pengelolaan dan Perlindungan Lahan Gambut - Eko Nuriyatman; Arrie Budhiartie; Latifah Amir (Jurnal USM Law Review)
This article aims to evaluate the effectiveness of the implementation of legislation in the management and protection of peatlands in Tanjung Jabung Timur Regency, as well as to identify the main obstacles and legal strategies that can be applied to overcome them. The background of the issue highlights that peatlands have significant ecological functions, particularly in maintaining environmental balance and mitigating climate change. Their existence faces serious threats due to land conversion, fires, and uncontrolled exploitation. The urgency of this research lies in the need to review the effectiveness of the regulations that have been implemented to ensure the sustainability of the peatland ecosystem functions, as well as the balance between utilization and environmental conservation. This research adopts a normative juridical approach with a descriptive-analytical method. The data used consists of secondary data obtained through a literature study of legislation, court decisions, scientific journals, and relevant policy documents. The novelty of this study lies in its specific focus on examining the implementation of legal regulations in peatland management in Tanjung Jabung Timur Regency, differing from previous studies that have been more general at the national level. The research findings indicate that the main obstacles in the implementation of peatland management laws include weak law enforcement, regulatory overlaps, conflicts of interest, and low public legal awareness. To address these challenges, optimal strategies are required, including strengthening coordination among state institutions, harmonizing regulations, enforcing strict sanctions, and utilizing technology for monitoring and law enforcement. With these strategies, it is expected that a balance between the utilization and protection of peatlands can be achieved in accordance with the principles of sustainable development.